Anesthetic considerations for rigid bronchoscopy: A narrative educational review. (April 2022) - Galway, Ursula; Zura, Andrew; Wang, Mi; Deeby, Magdelaine; Riter, Quinton; Li, Tianyun; Ruetzler, Kurt
Abstract: The advent of advanced diagnostic bronchoscopy has resulted in an increased demand for anesthesiologists to administer general anesthesia in the bronchoscopy suite. One such procedure includes rigid bronchoscopy. Rigid bronchoscopy is used to treat central airway lesions, mechanical debulking of endobronchial lesions, laser and argon plasma coagulation, electrocautery, cryotherapy, and stent deployment. Rigid bronchoscopy presents added challenges to the anesthesiologist due to the unusual nature of airway management and ventilation. Some of the challenges of providing anesthesia for rigid bronchoscopy include the need to share the airway with the proceduralist, the risk of loss of airway patency, unconventional modes of ventilation, and the need for a deep level of anesthesia with muscle relaxation. There is also a need for a quick recovery as many of these procedures are performed on an outpatient basis. Thus, knowledge of the rigid bronchoscopic procedure and excellent communication with the proceduralist is key to increasing the likelihood of a successful intervention This manuscript presents anesthetic considerations for rigid bronchoscopy and discusses how they may differ from other airway procedures.